Adult social care managers speak out: Exploring leadership development. (9th May 2021) - McCray, Janet; Temple, Paul Furness; McGregor, Suzanna
Abstract: As part of a 2‐year research project, 79 interviews were undertaken with adult social care (ASC) registered managers (RMs) in England. The study aimed to identify the factors that influence the leadership practice and priorities of RMs in their role in ASC at two points, before and after a leadership development programme (LDP). A critical framework of Bourdieu is used to explore and analyse how the RM's disposition plays out as they lead in the ASC sector. A narrative inquiry methodology was applied. Results found that a lack of funding and increasing regulation has added emotional stress to the RM leadership role and their motivation to lead. In order to cope, addressing the localised leadership development needs of the RMs was central and emotional wellness key. There is the potential for the ASC home to become a social arena for conflict between differing agency power relationships. By experiencing their preferred LDP, the RMs had gained insights into their position as a leader in ASC and how, by their own actions, they could both influence and shape it.